Gli orientamenti „Per vino nuovo otri nuovi”alla luce .del personalismo assiologico di D. von Hildebrand - Niewiadomski, Krzysztof (Warszawskie Studia Teologiczne, 2019)
The author of the article analyses the guidelines of the Congregation for Institutes of Consecrated Life and Societies of Apostolic Life New Wine in New Wineskins from the point of view of axiological personalism. This document looks with a critical eye at many realities of consecrated life in order to overcome its contemporary problems. It is possible to see structures of religious communities also in the light of Hildebrand’s theory of moral substitutes. To prevent axiological disturbances of the communities of consecrated life – individual conversion of their members is not enough but structural reforms are needed.